2017
DOI: 10.1038/nature23664
|View full text |Cite
|
Sign up to set email alerts
|

Human iPS cell-derived dopaminergic neurons function in a primate Parkinson’s disease model

Abstract: Induced pluripotent stem cells (iPS cells) are a promising source for a cell-based therapy to treat Parkinson's disease (PD), in which midbrain dopaminergic neurons progressively degenerate. However, long-term analysis of human iPS cell-derived dopaminergic neurons in primate PD models has never been performed to our knowledge. Here we show that human iPS cell-derived dopaminergic progenitor cells survived and functioned as midbrain dopaminergic neurons in a primate model of PD (Macaca fascicularis) treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
477
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 592 publications
(497 citation statements)
references
References 46 publications
20
477
0
Order By: Relevance
“…In terms of generating DA neurons, human iPSCs are very similar to hESCs in that they respond to the same differentiation cues and generate mature cells with very similar functional properties (Doi et al, 2014;Kikuchi et al, 2017;Kriks et al, 2011). Also in these studies, markers that predict a good outcome have been identified and shown to overlap with the predictive markers identified using hESCs .…”
Section: Other Cell Types Of Interest On the Horizonmentioning
confidence: 79%
See 1 more Smart Citation
“…In terms of generating DA neurons, human iPSCs are very similar to hESCs in that they respond to the same differentiation cues and generate mature cells with very similar functional properties (Doi et al, 2014;Kikuchi et al, 2017;Kriks et al, 2011). Also in these studies, markers that predict a good outcome have been identified and shown to overlap with the predictive markers identified using hESCs .…”
Section: Other Cell Types Of Interest On the Horizonmentioning
confidence: 79%
“…Experience gained from these pioneering clinical trials will guide the design of new and better cell-based treatments for PD, and hopefully also pave the way for developing stem cell based therapies for other neurological disorders. (Kirkeby et al, 2017b;Studer, 2017;Takahashi, 2017) • Tumorigenicity Rule out pluripotent cells or other contaminants in vitro and ensure no tumor formation in vivo can be done in nude mice or rats at certified contract research organization • Biodistribution Standard in vivo testing at certified CRO • Toxicology Standard in vivo testing at certified CRO (Kirkeby et al, 2017b;Studer, 2017;Takahashi, 2017) • Yield Estimate the number of mature dopaminergic neurons obtained per 100,000 grafted cells • Ability to restore motor function Full recovery of amphetamineinduced rotations in 6-hydroxydopamine lesion model • Long-range target specific innervation Intranigral grafting in rat model, or intrastriatal grafting in a large animal model (Barker et al, 2017;Grealish et al, 2014;Kikuchi et al, 2017) …”
Section: Discussionmentioning
confidence: 99%
“…Presently, it has been shown that introduction of several TFs (OKSM factors or Yamanaka factors) into somatic cells can reprogram and convert them with pluripotency [63,64]. Very recently, it was experimentally shown that iPS cellderived dopaminergic neurons could be applied for the treatment of Parkinson's disease [65]. These experimentally supported evidences suggest that introduction of certain combination of TFs into cancer cells might enforce them to reprogram transcription profile so that they could stop proliferation but acquire DNA repair with more accuracy.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Cell reprogramming and the therapeutic applications of induced pluripotent stem cells (iPSCs) remain a cutting edge research area (Normile 2017;Choi et al 2017;Kikuchi et al 2017). The promise and challenges of implementing this technology has also been covered in CBT (Devine and Patani 2017;Kim et al 2016;Driessen et al 2017).…”
Section: Implementation Of Induced Pluripotent Stem Cell/cell Reprogrmentioning
confidence: 99%
“…Devine and Patani provided a very useful, focused overview of the application of iPSC technology for neurological applications. Neurodegenerative diseases are predicted to become an increasing burden on society, and iPSCs can be used to generate disease models for compound screening to identify new drug candidates, such as Parkinson's disease and, notably, Zika virus infection (Kikuchi et al 2017;Xu et al 2016). Devine and Patani also describe the latest progress in scaling up the production of therapeutically relevant cell types derived from iPSCs for cell therapy applications, for example, developing 3D cultures that allow the harvesting of billions of uniform, mature neurons from a single flask (Rigamonti et al 2016).…”
Section: Implementation Of Induced Pluripotent Stem Cell/cell Reprogrmentioning
confidence: 99%